2009
DOI: 10.1111/j.1439-0310.2009.01716.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternity Loss in Relation to Male Age, Territorial Behaviour and Stress in the Pied Flycatcher

Abstract: For sexual selection to operate in monogamous species, males of poor quality in some factor like age, ornamentation, condition or aggressiveness, should lose paternity compared with higher quality males. We tested this idea in an Iberian population of pied flycatchers (Ficedula hypoleuca). Microsatellite analysis of 67 broods revealed moderate levels of extra-pair paternity (22.4% of broods, 7.5% of young). In a sample of 58 broods for which the caring male was identified, a higher paternity loss was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 58 publications
(144 reference statements)
6
44
4
Order By: Relevance
“…These studies have showed that when a stressor agent is present, corticosterone concentration is 2-17 times higher than in control treatments where stress agents are absent (Buchanan, 2000;Romero, 2004;Thiel et al, 2008;Moreno et al, 2010). For example, Dickcissels (Spiza americana) with corticosterone concentrations ∼6 ng/g in the absence of stressor agents, increased their values to ∼102 ng/g when they where subject to a stressor agent (Kimberly et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…These studies have showed that when a stressor agent is present, corticosterone concentration is 2-17 times higher than in control treatments where stress agents are absent (Buchanan, 2000;Romero, 2004;Thiel et al, 2008;Moreno et al, 2010). For example, Dickcissels (Spiza americana) with corticosterone concentrations ∼6 ng/g in the absence of stressor agents, increased their values to ∼102 ng/g when they where subject to a stressor agent (Kimberly et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Before discussing the implications of our findings, we should briefly consider if extra-pair fertilisations, which being relatively frequent in pied flycatchers (Lifjeld et al, 1991;Gelter and Tegelströ m, 1992;Brü n et al, 1996;Moreno et al, 2010), could be biasing our estimates of resemblance. Our data on extra pair fertilisations (D Canal, J Potti and JA Dávila, paper under review) do not allow for a proper estimation of their effect on trait heritability because of a combination of two events with low frequency, that is, recruiting to adult age (which is needed for the ornament being measured; average recruitment rate ¼ 14%, both sexes combined; N ¼ 14 years and 4536 fledglings; Montalvo, 1991b, Lehtonen et al, 2009) and being sired by a male other than the social 'father' (average rate of extra-pair paternity about 15%; D Canal and J Potti, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a few studies indicates that pair separation or mating with an unattractive partner increases circulating levels of corticosterone (Angelier et al 2007;Griffith, Pryke, & Buttemer, 2011;RemageHealey et al 2003). Higher levels of faecal corticosterone metabolites (Moreno et al 2010) and baseline corticosterone (Villavicencio, Apfelbeck, & Goymann, 2014) are also found to be associated with a greater loss of paternity in males. In white-throated sparrows, Zonotrichia albicollis, during the parental/nestling phase whitestriped morph males have higher levels of baseline corticosterone than tan-striped males (Horton & Holberton, 2010;Swett & Breuner, 2008), and white-striped males also have more extrapair fertilizations and provide less parental care than the tan-striped males (Tuttle, 2003).…”
mentioning
confidence: 94%